Pengaruh Pemberian Buku Saku Kendali Kebakaran (Busa Kekar) Terhadap Pengetahuan Kebakaran Karyawan Teknik PT Konimex - Maria Paskanita Widjanarti; Marcellina Kamillia; Erindra Budi Cahyanto (Journal of Applied Agriculture, Health, and Technology, 2023)
The Pharmaceutical Industry has a high risk of fire initiated by flammable chemicals, electrical energy and heat energy for production purposes. Fire Prevention Management must be carried out to manage the energy that causes fires. Fire prevention efforts, such as increased knowledge, availability of fire prevention infrastructure, and simulation activities, need to be conducted to increase the alertness of workers. Workers have an essential role in dealing with fires. Workers in engineering departments with activities that carry many risks of burning must be given knowledge in dealing with fires. They need to understand and analyse hazardous conditions in the workplace to apply fire extinguisher measures in the workplace. This study provides an intervention in the Fire Control Pocket Book (BUSA KEKAR) and its effect on fire control knowledge among technical employees at PT Konimex. A quasi-experimental method with a research design in the form of a posttest-only control design was used in this study. The experimental group was given intervention in the form of a Fire Control Pocket Book (BUSA KEKAR), while the control group was not assigned any intervention. The Experimental Group consisted of 35 people. Analysis of the Mann-Whitney test was carried out on the post-test results of the experimental group and the control group. There was an effect of giving the Fire Control Pocket Book (BUSA KEKAR) intervention on fire knowledge between the experimental group and the control group (p = 0.000).